Customer Satisfaction through Brand Image, Price, and Service Quality: Kepuasan Pelanggan Melalui Citra Merek, Harga, dan Kualitas Layanan - Firnanda, Rieke Ayu; Prapanca, Detak (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid growth of the fashion retail industry in Indonesia reflects the increasing consumer demand for modern, stylish, and high-quality products. Specific Background: Matahari Department Store, as one of Indonesia’s leading fashion retailers, faces challenges in maintaining customer satisfaction due to intense market competition and evolving consumer preferences. Knowledge Gap: Despite the growing competition in retail, limited studies have comprehensively examined the simultaneous role of brand image, price, and service quality in shaping customer satisfaction at local department stores. Aims: This study aims to determine how brand image, price, and service quality contribute to customer satisfaction at Matahari Department Store Sidoarjo. Results: Using a quantitative descriptive method with 96 respondents and SPSS 22 for analysis, the findings reveal that all three variables—brand image, price, and service quality—have a significant and positive relationship with customer satisfaction. Novelty: The research provides empirical evidence on how these factors jointly strengthen customer loyalty in the Indonesian retail fashion context. Implications: The findings encourage retail managers to focus on consistent brand identity, competitive pricing, and service excellence to sustain customer satisfaction. <article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:b33c4fad-0554-437c-8891-c6771d4ee003-1" data-testid="conversation-turn-4" data-scroll-anchor="false" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="13de849e-e3d3-4f46-9e67-4e4a1b382b4b" data-message-model-slug="gpt-5"> Highlights: Brand image, price, and service quality significantly shape customer satisfaction. Retail loyalty depends on brand trust and perceived service value. Findings guide competitive strategy in Indonesian fashion retail. Keywords: Brand Image, Price, Service Quality, Customer Satisfaction, Retail Fashion